Pluralism and local law in extraterritorial spaces. Issue 1 (14th March 2023) - Bochmann, Annett
Abstract: Based on ethnographic research, this article shows how legal orders are being established in spaces where the state law is absent. The case of refugee camps—often discussed as sites of legal limbo and state of exception—seems to be a space of legal pluralism. However, when observing local legal practices, this pluralism is dissolved into a powerful local camp law. This characteristic type of legal order is produced by social camp‐specific mechanisms, camp materiality as well as the remaking of pre‐camp structures. Therefore, refugee camps should be viewed as extraterritorial spaces with a high degree of legal autonomy that enables and forces residents to create a local camp law. The findings of this study add to the literature of law and order in camps and to the debates on plural configurations in extraterritorial spaces.